دور تمكين العاملين في تحسين جودة الخدمة الصحية دراسة حالة مصحة وادي ريغ بتقرت - بن شنة, وسيلة; برقيقة, يمينة; زموري, كميلية (University of eloued جامعة الوادي, 2019)
"تهدف هذه الدراسة إلى معرفة مستوى ودور تمكين العاملين في تحسين جودة الخدمة الصحية بمصحة وادي ريغ بتقرت، ولتحقيق أهداف الدراسة تم بناء استبيان مكون من 44 فقرة تشتمل ستة أبعاد لتمكين العاملين والمتمثلة في (التدريب، التفويض الكافي للصلاحيات، العمل الجماعي، التحفيز، إمتلاك المعرفة، الإستقلالية في إتخاذ القرار)، وخمسة أبعاد لجودة الخدمة الصحية والمتمثلة في (الملموسية، الإعتمادية، الإستجابة، الأمان، التعاطف). وقد اشتملت عينة الدراسة على 61 عامل بالمصحة محل الدراسة ممثلين في ( إداريين، ممرضين، مساعدي تمريض، أطباء) واعتمد في تحليل بيانات الاستبيان على التحليل الإحصائي الوصفي باستخدام برنامج الحزمة الإحصائية للعلوم الإجتماعية. وأظهرت نتائج الدراسة الميدانية ما يلي : - يوجد دور ذو دلالة معنوية لتمكين العاملين في تحسين جودة الخدمة الصحية بمصحة وادي ريغ بتقرت. ""The aim of this study is to determine the level and role of empowering workers in improving the quality of health services at the Wadi Righ clinic in Touggourt. To achieve the objectives of the study, a 44-padrgraph questionnaire was constructed which includes six dimensions for the empowerment of workers, namely: (training, adequate delegation of authority, teamwork, motivation, knowledge acquisition , Autonomy in decision-making) and five dimensions of quality of health service, namely: (tangibility, reliability, responsiveness, safety, empathy). The study sample consisted of 61 health workers in the clinic, represented by (administrators, nurses, nursing assistants, doctors). The sample was analyzed in descriptive statistical analysis using the statistical package program for social sciences. The results of the field study showed the following: - There is a significant role to enable the workers in improving the quality of health service in the clinic of the valley of Wadi Righ clinic. "
مذكرة ماستر ادارة اعمال
Keywords: تمكين العاملين، جودة الخدمة الصحية، مؤسسة صحية، مصحة وادي ريغ بتقرت.; Empowerment of Employees, Quality of Health Service, Health Foundation, Wadi Righ clinic in Touggourt.